Detection and Quantification of Auxin and Gibberellic Acid in Caulerpa racemosa - Dumale, J. V.; Gamoso, G. R.; Manangkil, J. M.; Divina, C. C. (International Journal of Agricultural Technology, 2018)
This study was conducted to evaluate plant growth regulators (PGRs) presented in extract of seaweed, Caulerpa racemosa by Spectrophotometry. Spectra were recorded at the m/z peak of 220 nm for Auxin, and at 524 nm m/z peak for Gibberellic acid in seaweed extract. Extraction, purification and quantitative determination of free and bound NAA, and GA3, in C. Racemosa were done by reducing 250 mL seaweed supernatant to 50 mL by evaporation and acidified to pH 2.8 with 1 N HCl and extracted with double volume of ethyl acetate. On the otherhand, GA3 was extracted and purified. Fifty mL of cell free supernatant was reduced to 20 mL by evaporation and acidified at pH 2 and then was extracted with double volume of chloroform. The supernatant was harvested by centrifugation and reduced to 30 mL by evaporation under vacuum. All experiments were repeated three times. Statistical analysis performed using SPSS statistical software (SPSS Inc., USA) for correlation and regression analysis of each value. The extract contained 979.71 mg/l of GA3 and 15.57 mg/l of NAA at 10 ppm concentration respectively. The results confirmed the presence of plant growth regulators (PGRs) (NAA, and GA3).